Sekularisme dalam parti politik Islam di Indonesia: Kajian terhadap Partai Kebangkitan Bangsa dan Partai Amanat Nasional / Mohamad Latief - Mohamad Latief, - (2016)
Secularism is an ethical system founded on the principle of natural morality and independent of revealed religion or supernaturalism. In the political realm, secularism is generally defined as a concept that exhorts the separation between religion and state. This research seeks to elucidate political secularism in two Islamic parties in Indonesia: Partai Kebangkitan Bangsa and Partai Amanat Nasional that traditionally enjoy a historical connection with Nahdlatul Ulama and Muhammadiyyah. This research is qualitative employing inductive, deductive and analytical-critical methods for analyzing the data. It is a combination of both library and field research. Data was collected through documentation compiling books, papers, articles and the likes, and open interviews. Through applying these methods, the study figures out that both PKB and PAN are of substantive Islamic parties conceiving a symbiotic-mutualistic construct of relation between Islam and state; each of which is inseparable and yet irreconcilable. The study also discovers certain elements of political secularism in both parties. Among these elements are the parties’ stance in placing Islam on a par with the other religions and their reluctance in rendering it as the sole ideology. PKB and PAN furthermore declare themselves as open and inclusive parties not confining their membership only to the Muslims. The membership is also open to the non-Muslims. Such political secularism is also apparent in their political culture in that Islam declines to be the source of political legitimacy being substituted by both democracy and nationalism. This secularism on political culture is becoming even worse as Islam ceases to be the identity of PKB and PAN as Islamic parties. Both parties are disinclined to be designated as Islamic and concurring with their agglomeration as national, open and inclusive parties instead. The study also discloses that the apparent political secularism in PKB and PAN is inflicted by various factors like leadership, government and the 1970s’ Muslim intellectuals. On the one hand, these three factors have successfully harmonized Islam and democracy or nationalism, but on the other, they overthrown the Islamic ideology and identity of PKB and PAN.